Classwide peer tutoring for elementary and high school students at risk: listening to students' voices. Issue 1 (February 2014) - Ayvazo, Shiri; Aljadeff‐Abergel, Elian
<x xml:space="preserve">Abstract</x> Teaching has become a very challenging profession with the requirements to provide appropriate individualised instruction in large and diverse classes. Problem behaviours displayed by students with special needs exacerbate the difficulties. This is especially true and intense in physical education, where students are exposed to extreme emotional situations under physical demands. Classwide peer tutoring (CWPT) is an evidence‐based teaching strategy that involves programmed interactions between peers and holds promise for the education of students at risk who display antisocial behaviours. This article discusses the implementation and modification of CWPT in third and eighth grades in a K‐12 inner‐city charter school in the USA, directed towards students who have special educational and social needs. First, the two CWPT applications are described. Second, authors share the students' reactions to the pedagogy. Third, based on students' responses and the teacher's accumulated experience delivering CWPT, the article discusses how to tailor CWPT better to each of the grade levels.